Experimental study of surface segregation and wetting in films of a partially miscible polymer blend - Geoghegan, M; Jones, R; Sivia, D; Penfold, J; Clough, A (1996)
We have studied composition-depth profiles in thin films of blends of deuterated polystyrene and poly(α-methyl styrene) using neutron reflectometry and 3He nuclear reaction analysis. Some of the neutron reflectometry data are analyzed using a maximum entropy technique with Bayesian probability. One blend is miscible for all compositions at the temperature studied (180°C), and we are able to obtain a bare surface energy difference between the two polymers from the equilibrium surface profile. The other blend that is studied is partially miscible, and here we have compared the approach to wetting in this blend with a simple model based on mean field theory. For quenches deeper into the metastable region of the phase diagram, the simple model fails due to, we believe, a competition between wetting and bulk nucleation and growth.